2001
DOI: 10.1016/s0022-5347(05)65648-0
|View full text |Cite
|
Sign up to set email alerts
|

Early Removal of the Catheter After Laparoscopic Radical Prostatectomy

Abstract: Patients who undergo laparoscopic radical prostatectomy can have the catheter safely removed 2 to 4 days postoperatively without a higher risk of incontinence, stricture or leak related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 8 publications
5
60
0
3
Order By: Relevance
“…Similar results were reported by Santis et al 13 who removed the catheter successfully 8 or 9 days after the surgery without cystography. Also, these results are to some extent supported by the study of Nadu et al , 7 who demonstrated in a large series of cases the absence of leaks in 84.9% of the individuals who underwent cystography 2 to 4 days after radical prostatectomy.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Similar results were reported by Santis et al 13 who removed the catheter successfully 8 or 9 days after the surgery without cystography. Also, these results are to some extent supported by the study of Nadu et al , 7 who demonstrated in a large series of cases the absence of leaks in 84.9% of the individuals who underwent cystography 2 to 4 days after radical prostatectomy.…”
Section: Discussionsupporting
confidence: 63%
“…Also, it is our opinion that the cases of hematuria and urinary retention are acceptable events, since these can be easily solved by reposition of the catheter for longer periods. 6,7 In summary, considering some potentially limiting factors such as the relatively small size of the present series and the short period of follow-up, the results of the present study indicate that a period of 7 days of catheterization is probably enough after RRP, since catheter withdrawal after this period was not associated with a higher rate of complications than were experienced by the group of patients who had their catheters removed at the standard fashion (14 days after surgery).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Early recatheterization after radical prostatectomy (RP) is required in cases of acute urinary retention or disruption of vesicourethral anastomosis, after catheter removal, and in cases of incidental displacement of the catheter [1][2][3][4]. In addition, malfunction in draining the bladder requires immediate catheter replacement.…”
Section: Introductionmentioning
confidence: 99%